Curriculum renewal in acute care: a South African based study for returning Cuban-trained students - Khan, Waseela (Department of Health Sciences Education, 2025)
Background: Emergency Care plays an integral role in Universal Health Coverage (UHC), yet several limitations have been identified in Low- and Middle-Income Countries (LMIC), one of which is the lack of dedicated, integrated curricula. In 1996 the Nelson Mandela Fidel Castro (NMFC) student program was developed in response to societal health needs for equitable health care in rural and under-served areas, affirmative action, and the low doctor-to-population ratios nationally. Cuban medical education is Primary Health Care focussed and not aligned with Acute Care competencies. This study explores the NMFC students' needs, the barriers to learning, and the role of transition in this process, as a first integral step in curriculum renewal in Acute Care. Methods: A qualitative approach of focus group interviews with 18 UCT NMFC students and semi-structured interviews with preceptors was conducted. Data was then analysed thematically and with the lens of the chosen theoretical framework framed by Transition theory and Situated Learning theory. Results: The findings indicate that skills and simulation-based teaching methodologies are favoured. A structured orientation within an Acute Care transition program and supervised and integrated workplace supervision is needed. Barriers to student learning include time, a perceived sense of ‘othering,' and educational ‘differences' to Cuban training. NMFC students were identified for their willingness to learn. Preceptors further identified a lack of dedicated time for Acute Care and a lack of resources as barriers to facilitation. Conclusions: As socially responsible educators we must be considerate of student needs and respond with a robust curriculum. The challenge is designing a curriculum in Acute Care that addresses the specific learning needs of a group of designated adult learners from previously disadvantaged backgrounds, transitioning between institutions with different educational outcomes, in the care of undifferentiated critically ill patients, within the short timeframes in resource-constrained educational and health institutions. Recommendations include the addition of a robust transition program to integrate, orientate and scaffold Acute Care knowledge and skills deficits. The curriculum must include skills and simulation-based methodologies for ‘hands-on' practice, opportunities for self-directed learning, and situated learning within supportive communities of practice.